THE IMPORTANCE OF HYDRATION AWARENESS FOR VOLLEYBALL PLAYERS - Ahmad Hariyanto (International Journal of Social Science, 2023)
When playing volleyball, there is an optimal mechanism in terms of dissipating heat energy from the body, which will evaporate sweat from the surface of the skin. This mechanism is also versatile in regulating temperature ranges in the body, where this process occurs during the sweating phase which can have an effect on dehydration. Dehydration itself is part of the loss of fluid volume in the body so that it can experience changes in body mass that occur during exercise. For example, water dehydration of 2% is defined as a body mass deficit of 2%. Thermoregulation in sweat is the main source of loss of body mass during acute exercise/exercise, but there are other factors that contribute, namely the loss of water and carbon dioxide through the respiratory tract which is produced by the substrate oxidation pathway. To restore stamina optimally as a result of rehydration, there must be a strategy to restore this condition. It is known that rehydration is an important factor in recovery, especially after exercise, if a player experiences a body mass deficit, they must replace it with fluids and electrolytes in preparation for the next training or match